2008
DOI: 10.1002/chem.200800300
|View full text |Cite
|
Sign up to set email alerts
|

Squaraines as Reporter Units: Insights into their Photophysics, Protonation, and Metal‐Ion Coordination Behaviour

Abstract: The synthesis, photophysical properties, protonation, and metal-ion coordination features of a family of nine aniline-based symmetrical squaraine derivatives are reported. The squaraine scaffold displays very attractive photophysical properties for a signalling unit. These dyes show absorption and weakly Stokes-shifted, mirror-image-shaped emission bands in the visible spectral range and there are no hints of multiple emission bands. The mono-exponential fluorescence decay kinetics observed for all the derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 136 publications
1
40
0
1
Order By: Relevance
“…38-43 These properties allow many applications from dye-sensitized solar cells and organic photovoltaic applications 32, to ion sensors [67][68][69][70][71] and biolabelling. [72][73][74][75][76][77][78][79][80] Unlike conjugated polymers that are based on very small monomers such as styrene (e.g., MEH-PPV) or thiophene (e.g., P3HT) and whose polymer properties are totally different from those of the monomers, 81 squaraine homo-and copolymers are based on squaraine dyes which already show a strong absorption in the red region of the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…38-43 These properties allow many applications from dye-sensitized solar cells and organic photovoltaic applications 32, to ion sensors [67][68][69][70][71] and biolabelling. [72][73][74][75][76][77][78][79][80] Unlike conjugated polymers that are based on very small monomers such as styrene (e.g., MEH-PPV) or thiophene (e.g., P3HT) and whose polymer properties are totally different from those of the monomers, 81 squaraine homo-and copolymers are based on squaraine dyes which already show a strong absorption in the red region of the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Thus, squaraines are a widely used class of functional dyes for a huge variety of applications. [8] Squaraines have been used in single-layer OPVs and, more recently, in vacuum-deposited and dye-sensitized solar cells. [9] Lately, Silvestri et al reported for the first time on the use of squaraines in solution-processable BHJ solar cells with PCEs of up to 1.2 %.…”
mentioning
confidence: 99%
“…However, based on the work of Ros-Lis et al , protonation on the oxygen atom would result in a slightly red shifted and/or greatly blue-shifted absorption band accompanied by a reduction in the intensity of the normal absorption band. 71 We checked the absorption spectra of our G0Sq monomer in acidic solutions, and found only the main peak at around 640 nm decreased in intensity, and no new absorption band was found (Fig. S3†), thus indicating that the protonation was on the nitrogen atom.…”
Section: Resultsmentioning
confidence: 98%